A report on the status of vaccination in Europe. Issue 33 (9th August 2018) - Sheikh, Shazia; Biundo, Eliana; Courcier, Soizic; Damm, Oliver; Launay, Odile; Maes, Edith; Marcos, Camelia; Matthews, Sam; Meijer, Catherina; Poscia, Andrea; Postma, Maarten; Saka, Omer; et al.
Highlights: There is an individual approach to vaccination across the 16 European countries. Most countries prioritise paediatric immunisation (set targets, monitor coverage). Additional measures to improve vaccine coverage in all age groups are needed. Harmonisation in target setting and data collection was proposed (European Vaccine Action Plan 2015–2020). EVAP 2015–2020 proposition has been adopted but not yet implemented to date. Abstract: Vaccine policy, decision processes and outcomes vary widely across Europe. The objective was to map these factors across 16 European countries by assessing (A) national vaccination strategy and implementation, (B) attributes of healthcare vaccination systems, and (C) outcomes of universal mass vaccination (UMV) as a measure of how successful the vaccination policy is. A. Eleven countries use standardised assessment frameworks to inform vaccine recommendations. Only Sweden horizon scans new technologies, uses standard assessments, systematic literature and health economic reviews, and publishes its decision rationale. Time from European marketing authorisation to UMV implementation varies despite these standard frameworks. Paediatric UMV recommendations (generally government-funded) are relatively comparable, however only influenza vaccine is widely recommended for adults. B. Fourteen countries aim to report annually on national vaccine coverage rates (VCRs), as well as have target VCRs per vaccine across different age groups. Ten countries use either electronic immunisation records or a centralised registry for childhood vaccinations, and seven for other age group vaccinations. C. National VCRs for infant (primary diphtheria tetanus pertussis (DTP)), adolescent (human papillomavirus (HPV)) and older adult (seasonal influenza) UMV programmes found ranges of: 89.1% to 98.2% for DTP-containing vaccines, 5% to 85.9% for HPV vaccination, and 4.3% to 71.6% for influenza vaccine. Regarding reported disease incidence, a wide range was found across countries for measles, mumps and rubella (in children), and hepatitis B and invasive pneumococcal disease (in all ages). These findings reflect an individual approach to vaccination by country. High VCRs can be achieved, particularly for paediatric vaccinations, despite different approaches, targets and reporting systems; these are not replicated in vaccines for other age groups in the same country. Additional measures to improve VCRs across all age groups are needed and could benefit from greater harmonisation in target setting, vaccination data collection and sharing across EU countries.